2017
DOI: 10.1177/1356336x17746949
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a special school placement on self-perceptions of confidence and competence among prospective PE teachers

Abstract: 5School-based placements are often used as a way of preparing prospective teachers for the 6 demands of their future role. However, little is known about the impact of such situated 7 learning experiences on prospective PE teachers' confidence and competence. To the best of 8 our knowledge, this article is the first of its kind to explore prospective teachers' views of, 9 and experiences within, special schools in order to identify the experiential mechanisms that 10 shape self-perceptions of competence and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…These findings support existing literature showing that situated learning experiences can help to improve the confidence and competence of teachers, including both prospective and preservice teachers, working in inclusive environments (Malinen et al , 2013; Sokal & Shrama, 2014; Maher et al , 2017). However, they show that in mainstream education settings, it is sometimes difficult for preservice teachers to identify pupils with SEND, or alternately, when they do, they do not have direct experience of working with these pupils.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings support existing literature showing that situated learning experiences can help to improve the confidence and competence of teachers, including both prospective and preservice teachers, working in inclusive environments (Malinen et al , 2013; Sokal & Shrama, 2014; Maher et al , 2017). However, they show that in mainstream education settings, it is sometimes difficult for preservice teachers to identify pupils with SEND, or alternately, when they do, they do not have direct experience of working with these pupils.…”
Section: Discussionsupporting
confidence: 87%
“…Further, when considering ITE within the UK context, where many preservice teachers enrol on a 1‐year postgraduate teacher education programme, there is little scope to develop standalone inclusion courses spanning the length of time available within 4/5‐year programmes offered internationally, such as in Canada, the USA and Australia. Scholars within the UK have, however, implemented direct‐experience elements within education programmes, the most recent being the work of Maher et al (2017). However, while positive outcomes in relation to confidence and competence were recognised, the field experience was offered on a bachelor’s degree programme with ‘prospective’ rather than in‐training teachers, and impact was determined through qualitative interviews and not measured statistically.…”
Section: Introductionmentioning
confidence: 99%
“…relationships between peers and school culture) (Ten Dam and Blom, 2006). It is expected that school placement prepares PSTs for their future demands (Maher et al, 2017). Therefore, school placement has been acknowledged as an emotional space when becoming a teacher due to experiencing both positive and challenging emotions (Timoštšuk and Ugaste, 2012; Zembylas, 2003a), with highs and lows (Meijer et al, 2011), related not only to the concept of ‘reality shock’ (Veenman, 1984) but also to PSTs’ expectations.…”
Section: Understanding Teachers’ Emotionsmentioning
confidence: 99%
“…In this respect, hands-on experience with children with disabilities is said to be key for developing positive attitudes towards inclusion and teaching pupils with disabilities (Coates, 2012). Maher et al (2017) are among a growing number of academics who have championed the use of special school-based placements for gaining this experience. However, it can be difficult to arrange special school based-placements because (1) so few are in close proximity to universities; (2) it can be problematic quality-assuring the 'PE' offered; and (3) some are already saturated with pre-service teachers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be difficult to arrange special school based-placements because (1) so few are in close proximity to universities; (2) it can be problematic quality-assuring the 'PE' offered; and (3) some are already saturated with pre-service teachers. Moreover, as Maher et al, (2017) found, some pre-service PE teachers are not adequately prepared for working in what can be the very challenging, albeit rewarding, learning environments of special schools, especially for those with limited previous exposure to children with disabilities.…”
Section: Introductionmentioning
confidence: 99%